THE IMPORTANCE OF THE ROLE OF HUMAN RESOURCE MANAGEMENT IN AN ORGANIZATION - Iswadi Iswadi; Erman Anom; Fachmi Tamzil (CV. Bunda Ratu, 2023)
We know that the role of human resource management greatly influences an organization. According to Psondang (2022) that an organization is an association consisting of two or more people. We often encounter organizations in the political, business, professional, and social fields. Not only found in these fields but also in the field of education. Like the organizations that exist in agencies, it really helps students in honing their skills and also their critical thinking. The organization was formed in order to achieve the goals of each team. This study will focus on strategies for managing human resources in organizations. The results of the analysis show that strategies can have a good impact on teams in organizations. As for strategies in managing human resources in an organization such as the ability to understand and interpret the wishes of superiors, have creative thinking, and have a broad outlook, this can improve the company itself. This research method uses a description method through published journals. Easy to manage in the corporate world, a sufficient level of team members is needed, with this the company can also work together with other companies.